Penerapan Metode Analytic Network Process Pada Pendukung Keputusan Pengangkatan Guru Tetap - Nurlela, Siti; Fania, Liza; Ananda, Aditya; Juanda, Muhammad; Sembiring, David JM (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The process of appointing honorary teachers as permanent teachers still faces various challenges, particularly concerning objectivity and transparency in decision-making. Many educational institutions continue to rely on manual evaluation methods to assess teacher eligibility, which are often subjective and lack measurable analytical foundations. Consequently, the appointment process does not always reflect the actual competence and performance of honorary teachers. Based on these issues, this study aims to develop a Decision Support System (DSS) based on the Analytical Network Process (ANP) method to assist schools and educational authorities in objectively, systematically, and accurately determining which honorary teachers are eligible for permanent appointment. The ANP method was chosen because it can map the interdependence among criteria and sub-criteria in the selection process. Data were collected through observation, interviews, and literature review, then processed using a pairwise comparison matrix to generate the priority weights of each criterion and alternative. The findings indicate that the ANP-based decision support system effectively improves speed, efficiency, and fairness in the teacher appointment process. The results show that the alternative Dwi Rokita achieved the highest score of 2.531439, making her the most eligible candidate for permanent appointment. Therefore, the application of the ANP method proves to be effective in supporting objective and accountable decision-making in the appointment of honorary teachers, while simultaneously contributing to the improvement of human resource quality in the education sector.